Genetic profiling of melanoma in routine diagnostics: assay performance and molecular characteristics in a consecutive series of 274 cases - Leichsenring, Jonas; Stögbauer, Fabian; Volckmar, Anna-Lena; Kirchner, Martina; Fröhling, Stefan; Hassel, Jessica C.; Enk, Alexander; Schirmacher, Peter; Endris, Volker; Penzel, Roland; Stenzinger, Albrecht (Pathology, 2018)
A deeper understanding of melanoma biology has opened up new avenues for mechanistically informed therapies. However, data on the prevalence of druggable genetic lesions in melanoma are still conflicting and real-world performance data on high-throughput genetic profiling of melanoma cases using formalin fixed, paraffin embedded (FFPE) tissue with variable tumour cellularity and quality are lacking. We retrospectively analysed targeted next-generation sequencing data of 274 consecutive melanoma samples obtained for routine diagnostics between December 2013 and July 2017. Actionable mutations were detected in 197 cases (71.9%), of which activating BRAF (mostly p.V600E/K) and RAS (mostly p.Q61R/K) mutations occurred in 40.5% (n = 111) and 30.3% (n = 83) of cases, respectively. We identified driver mutations of the Triple-WT subgroup in 10.6% of cases (n = 29; 10 with activating KIT mutations). Median turnaround time was 5 working days with no dropouts. Tumour cellularity ranged from 5% to 95% and successful sequencing was possible at DNA concentrations as low as 0.03 ng/μL (median 10.58 ng/μL; range 0.03-209.05 ng/μL). Fast, quality-controlled high-throughput genetic profiling of FFPE melanoma samples is feasible and provides a landscape of genetic aberrations in melanoma that is currently relevant in clinical practice and approximates TCGA subtypes.